Legal Legitimacy and Regional Governance: Lessons from Indonesia–PNG Diplomatic Engagements - Khoirunnisa Khoirunnisa; Didi Jubaidi (Jurnal Hubungan Internasional, 2026)
Abstract Indonesia and Papua New Guinea (PNG) share one of the most complex land borders in the Asia-Pacific region, where questions of sovereignty, security, and indigenous identity frequently intersect. This article examines how legal legitimacy shapes regional governance in the context of Indonesia–PNG diplomatic relations. Using a qualitative legal approach combined with policy and document analysis, the study draws on treaties, bilateral agreements, official diplomatic statements, and domestic legal instruments. The research finds that although diplomatic ties have gradually improved, legal and institutional asymmetries continue to limit the effectiveness of cross-border cooperation, particularly in managing population mobility, informal trade, and localized conflict. Nevertheless, recent developments such as Indonesia’s BNPP coordination mechanism and PNG’s ongoing legal reform efforts indicate potential for a more coherent and legitimate governance framework. By focusing on an often-overlooked bilateral relationship, this study contributes to a deeper understanding of diplomacy at the regional margins and highlights the centrality of legal design in fostering sustainable and trust-based cooperation between neighboring states. Keywords: Legal Legitimacy; Border Diplomacy; Indonesia–PNG Relations; Regional Governance; Transboundary Cooperation.